Implementasi Metode Reliability Centered Maintenance untuk Menunjang Ketersediaan Suku Cadang Unit Prime Mover Truck Tipe 550 Horse Power - Mahendra, Resa; Zainuri, Ach. Muhib (Lembaga Yasin AlSys, 2024)
One of mining materials transport units is a 550 horse power prime mover truck. The prime mover truck functions as the main power source of trailer unit. This research was motivated by unexpected failures of 550 horsepower prime mover truck which operating on extreme mining environments, and unreachable component lifetime also delays of part supply, which contributed to increased downtime. The research purposes are to improve and develop the best maintenance system by identifying critical components, determining reliability values, determine maintenance intervals, and ensuring spare parts availability. The research was conducted using the Reliability Centered Maintenance (RCM) method, with independent variables are failure frequency data and failure duration data. The results identified five critical components, air piping and hose, fast fuel filler, radiator components, radiator hose, and wheel stud and nut. Maintenance intervals were determined when the reliability value approached 0.6, with the air piping and hose component reaching 1750 hours of operation or every 97 days, the fast fuel filler component reaching 1,250 hours or every 69 days, the radiator and reservoir tank component reaching 2250 hours or every 125 days, the radiator hose and line component reaching 2750 hours or every 152 days, and the wheel stud and nut component of 3000 hours or every 166 days.